Ecophysiological characterization and molecular differentiation of Culex pipiens forms (Diptera: Culicidae) in Tunisia - Marwa Beji; Adel Rhim; David Roiz; Ali Bouattour (Parasites & Vectors, 2017)
Abstract Background The Culex pipiens complex (Diptera: Culicidae) includes the most widespread mosquito species in the world. Members of this complex are the primary enzootic and epidemic vectors of the West Nile virus (genus Flavivirus) in several countries. The two recognized forms of Cx. pipiens (Linnaeus, 1758) - pipiens and molestus - exhibit behavioral and physiological differences. Natural populations of Cx. pipiens were investigated in several sites in Tunisia to evaluate the ecophysiological and molecular characteristics of their forms. Results The analysis showed the sympatric presence of Cx. pipiens forms and hybrids in all studied sites. Of all the tested larvae of Cx. pipiens, 33.5% were identified as pipiens, 30.8% were identified as molestus, and 35.6% were identified as hybrids. The molestus and hybrid forms were positively correlated with urban habitats and belowground sites while the pipiens form was positively correlated with rural habitats and aboveground sites. Autogeny was expressed in all types of habitats and breeding sites. By contrast with the microsatellite CQ11, the two molecular markers, ace-2 and cytb, did not allow differentiation between the Cx. pipiens forms. Conclusions Our study shows the ubiquitous distribution and the plasticity of the different forms of Cx. pipiens in a wide range of ecological conditions. It suggests that the behavioral traits assigned to the forms of Cx. pipiens seem to be more flexible than previously assumed. Our analysis also proves that the microsatellite CQ11 remains an efficient tool for distinguishing between Cx. pipiens forms.